Legal Protection in Recovering Children from Victims of Sexual Violence - Agus Thohawi (Westscience Press, 2023)
Sexual violence against children is a social disaster that presents a serious problem that worries people in Indonesia. Sexual violence is a form of dangerous behavior that is carried out unilaterally and unintentionally by the victim through language, writing, symbols, gestures, or actions that have sexual meaning. Sexual violence against children can be in the form of cruelty to animals, rape, obscenity, and incest. Ideally, legal protection for child victims of various forms of sexual violence must be optimally achieved. According to the 1945 Constitution, the state has a legal obligation to guarantee children's rights to survival, growth, development and protection from violence and discrimination. The problem studied in this research is how legal protection is in recovering children from victims of sexual violence. This study uses descriptive-analytic legal research, the purpose of which is to provide an overview of the problem by processing and analyzing data to then obtain materials and problem-solving proposals. The conclusion of this study shows that legal protection in the recovery of children from sexual abuse is very important to ensure that children who experience sexual abuse get their rights and get the support and care they need to recover from this traumatic experience.